Formalin fixation and patterns of antineutrophil cytoplasmic antibodies. - Spickett, G P (1995)
Recent publications have suggested that fixing neutrophils in formalin is a useful adjunct to the differentiation of antinuclear antibodies from perinuclear antineutrophil cytoplasmic antibodies. In this small comparative study of 30 sera the use of an additional slide of formalin fixed neutrophils did not add any useful information and may be confusing as the results were not reproducible.